Detection of a New GeV Source in the Outer Region of the Coma Cluster: A Signature of External Accretion Shock? - Xiao-Bin Chen; Kai Wang; Yi-Yun Huang; Hai-Ming Zhang; Shao-Qiang Xi; Ruo-Yu Liu; Xiang-Yu Wang (The Astrophysical Journal Letters)
The supersonic flow motions associated with infall of baryonic gas toward sheets and filaments, as well as cluster mergers, produces large-scale shock waves. The shocks associated with galaxy clusters can be classified mainly into two categories: internal shocks appearing in the hot intracluster medium within the viral radius and external accretion shocks forming in the outer cold region well outside of the virial radius. Cosmic-ray (CR) electrons and/or protons accelerated by these shocks are expected to produce gamma rays through inverse-Compton scattering (ICS) or inelastic pp collisions, respectively. Recent studies have found a spatially extended GeV source within the virial radius, consistent with the internal shock origin. Here, we report the detection of a new GeV source at a distance of about 2 $\mathop{.}\limits^{\unicode{x000b0}}$ 8 from the center of the Coma cluster through the analysis of 16.2 yr of Fermi-LAT data. The hard spectrum of the source, in agreement with the ICS origin, and its location in a large-scale filament of galaxies points to the external accretion shock origin. The gamma-ray (0.1−10 ^3 GeV) luminosity of the source, 1.4 × 10 ^42 erg s ^−1 , suggests that a fraction  ~10 ^−3 of the kinetic energy flux through the shock surface is transferred to relativistic CR electrons.